PERAN FILSAFAT ILMU DALAM MENDORONG PERKEMBANGAN ILMU PENGETAHUAN - SALIM, AGUS; Larasati; Restiyanita; Syafaat, Anugrah Hisam (Jurnal Pendidikan Teknologi Informasi (J-Diteksi), 2025)
Philosophy of science is a branch of philosophy that studies the fundamental principles and methods underlying scientific knowledge. In the context of the rapid development of scientific knowledge, the philosophy of science plays a crucial role in providing a solid foundation to understand how knowledge is acquired, tested, and validated in an objective and rational manner. This article aims to examine the contribution of the philosophy of science in driving the development of scientific knowledge, focusing on its epistemological, ontological, methodological, ethical aspects, and the role of innovation in scientific research. The methodology used in this article is a qualitative approach with a descriptive analysis of relevant literature on the philosophy of science and its contribution to scientific knowledge. The philosophy of science not only helps in shaping scientific paradigms that guide researchers in formulating theories and conducting research, but also ensures that research is carried out while considering its social and moral implications. Therefore, the philosophy of science plays an essential role in ensuring that scientific knowledge develops in a systematic, responsible, and socially relevant manner.